Non-Keplerian orbits using hybrid solar sail propulsion for Earth applications - Heiligers, Jeannette; McInnes, Colin; Biggs, James; Ceriotti, Matteo (University of Strathclyde, 2012)
Half a century of space technology development has provided a wealth of new space applications. However, many still remain to be explored. Examples include increased geostationary coverage and new opportunities to enhance polar observation. This thesis investigates both of these opportunities using families of non-Keplerian orbits, while demonstrating the potential of hybridised solar sail and solar electric propulsion (SEP) to enable these orbits. Due to an increased number of geostationary spacecraft and limits imposed by east-west spacing requirements, GEO is starting to get congested. As a solution, this thesis creates new geostationary slots by displacing the geostationary orbit out of the equatorial plane by means of low-thrust propulsion. A full mission analysis and systems design is presented as well as an investigation of a range of transfers that can improve the performance of the displaced GEO and establish its accessibility. The analyses demonstrate that only hybrid propulsion can enable payloads to be maintained in a true geostationary orbit beyond the geostationary station-keeping box for lifetimes comparable to current GEO spacecraft. The second opportunity, enhancing polar observations, is investigated by designing optimal transfers from low Earth orbit (LEO) to an Earth pole-sitter orbit that allows the spacecraft to hover above the polar regions. Both high-thrust (upper-stage) and low-thrust (spiral) transfers are considered and show that hybrid propulsion increases the mass delivered to the pole-sitter orbit compared to a pure SEP case, enabling an extension of the mission. In addition, transfers between north and south pole-sitter orbits are investigated to overcome limitations in observations during the polar winters. Again, hybrid propulsion reduces the propellant consumption compared to pure SEP, while increasing the polar observation time. Overall, hybrid propulsion is proven an enabling propulsion method that can enable missions that are not feasible using only a solar sail and can ...